MOTOR ACTIVITIES USED IN THE PASAGE TO SITTING POSITION FROM THE SUPINE POSITION IN CHILDREN FROM SIX TO TWELVE MONTHS (Fiep Bulletin - online, 2013)
The study of child development neuropsychomotor, enables health professionals greater understanding of the motor behavior in childhood giving subsidies to a correct assessment and intervention for children with delays in motor development. Among the milestones of motor development, the ability of children to stay and move to the sitting position provides more space for infants to vary their behavior by encouraging their cognitive development. This study objective was to verify different ways to pass to sitting position, from supine position in healthy children, between the sixth and twelfth months of life. The sample comprised 180 children who attended municipal, state and private daycare centers of Balneario Camboriú, Camboriú, and Itajaí. Information obtained through the observation of motor activities used by children to achieve sitting voluntarily, was recorded in an evaluation form which was developed and validated by researchers previously. As the results, the passage to sitting position was observed for the first time in children from seven months, thus the predominant passages were the ones which passes through prone position. Passages using the lateral position with the support of the two upper limbs or only one, were mostly in children of older age strata. Although there is a tendency in the way of achieving the sitting position, it was observed variations within the same stratum, it reinforced the assumption that in addition to the neurological maturation, environmental influences and stimuli influence the time that the motor acquisitions happened.
Keywords: Motor development; chronological age; sitting position; physiotherapy.